2011
DOI: 10.1590/s0100-204x2011001200007
|View full text |Cite
|
Sign up to set email alerts
|

Herdabilidade e correlação fenotípica de caracteres relacionadosà produtividade de grãos e à morfologia da canola

Abstract: O objetivo deste trabalho foi estimar a herdabilidade e avaliar a correlação fenotípica entre caracteres de canola (Brassica napus) relacionados à produtividade de grãos e à arquitetura de plantas. Foram realizados três experimentos, com espaçamento entre linhas de 0,20, 0,40 e 0,60 m. Durante dois anos de cultivo (2008 e 2009), os genótipos 'Hyola 432' e 'Hyola 61' foram avaliados em quatro densidades de plantio (20, 40, 60 e 80 plantas por metro quadrado), em cada experimento. Empregou-se o delineamento de b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 15 publications
(11 reference statements)
3
10
0
7
Order By: Relevance
“…The variables measured were total dry matter (TDM, kg ha Data were examined by analysis of variance per location to obtain the mean squared values of the genotypes in the mean of the years of cultivation, involving, overall, the cumulative effect of years and locations in the model. This procedure is recommended by Krüger et al (2011) for ensuring consistency in the estimation of heritabilities and correlations. The mean square values were used to determine the genetic parameters, according to Carvalho et al (2001).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The variables measured were total dry matter (TDM, kg ha Data were examined by analysis of variance per location to obtain the mean squared values of the genotypes in the mean of the years of cultivation, involving, overall, the cumulative effect of years and locations in the model. This procedure is recommended by Krüger et al (2011) for ensuring consistency in the estimation of heritabilities and correlations. The mean square values were used to determine the genetic parameters, according to Carvalho et al (2001).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, path analysis comes up as a complementary technique indicating the true associations of cause and effect on the main variable of interest. This procedure aims to measure the true relationships such as in the components of grain yield of grain species (Lopez & Franke, 2011;Krüger et al, 2011), as well as forage species (Silva et al, 2008;Borges et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of adaptability and stability have been increasingly used in the identification of cultivars with more stable and predictable behavior regarding the environmental variations (Silva & Duarte, 2006), as well as in the definition of more adequate cultivation techniques (Krüger et al, 2011). It should be pointed out that there could be different responses between the methods of estimation of adaptability and stability (Cargnelutti Filho et al, 2007) as observed in the present study.…”
Section: Resultsmentioning
confidence: 59%
“…Rapeseed yield has great variations along the cultivation years. These variations can occur due to the differences in meteorological conditions from year to year (Dalmago et al, 2009), losses through natural threshing, due to uneven maturation of siliques (Silva et al, 2011) and management practices, such as sowing spacing and density (Shahin & Valiollah, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Constata-se que o aumento do espaçamento entre linhas promoveu alterações que se compensam nestas duas variáveis de forma conjunta a alterar resposta da planta para ajuste no dossel. A canola é uma espécie de hábito de crescimento indeterminado e que apresenta estruturas plásticas e ajustáveis na população (KRÜGER et al, 2011), assim como verifi cado também por JACOB JÚNIOR et al (2012). A fase vegetativa (DEIF) mostrou elevada contribuição e estabilidade, com similaridade de valores nos três espaçamentos (0.20, 0.40 e 0.60m) (Tabela 2).…”
Section: Resultsunclassified